2003
DOI: 10.1002/gps.944
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of ECT in depressed older adults: a literature review

Abstract: ECT is effective in the acute treatment of late life depression and is generally safe. Important questions such as the relative efficacy of ECT over antidepressants, the long-term efficacy of ECT, morbidity and mortality related to ECT, cost-effectiveness and the efficacy of ECT in subgroups of patients cannot be answered and need to be studied further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
6

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(46 citation statements)
references
References 108 publications
1
39
0
6
Order By: Relevance
“…ECT has been found to be highly effective in moderate to severe depression and depression with melancholic features [68]. ECT has been recommended as an initial treatment in patients who have depression with psychotic symptoms or catatonia, severe depressive symptoms and functional impairment, and comorbid medical problems, and when there is an urgent need for response (ie, patients who are acutely suicidal or patients who refuse food and are nutritionally compromised).…”
Section: Treatment With Electroconvulsive Therapymentioning
confidence: 99%
“…ECT has been found to be highly effective in moderate to severe depression and depression with melancholic features [68]. ECT has been recommended as an initial treatment in patients who have depression with psychotic symptoms or catatonia, severe depressive symptoms and functional impairment, and comorbid medical problems, and when there is an urgent need for response (ie, patients who are acutely suicidal or patients who refuse food and are nutritionally compromised).…”
Section: Treatment With Electroconvulsive Therapymentioning
confidence: 99%
“…2 Older age is associated with a better outcome, with remission rates reaching 73%-90% in patients older than 65 years. 3,4 Electro convulsive therapy has a positive effect on mood, cognition and psychomotor function in elderly patients with depress tion, is considered safe 5,6 and is recommended as a preferen tial treatment for major depression with psychotic features, treatmentresistant depression and acute suicidal ideation. 7 Despite these welldocumented clinical effects in patients with late life depression (LLD), little is known about the brain changes associated with ECT in elderly patients.…”
Section: Introductionmentioning
confidence: 99%
“…ECT remission rates in geriatric depression are high (50-90 %) [26][27][28] and appear to be higher than in younger depressed populations. A large prospective study (n=253) comparing the efficacy of bitemporal (BT) ECT in older and younger patients found that the elderly presented higher remission rates (90 % in ≥65 years vs 75 % in ≤45 years) and identified age as a significant predictor of superior antidepressant response, after adjusting for psychosis, severity and number of prior episodes [26].…”
Section: Individual Factors: Agementioning
confidence: 99%